Pengaruh Pengungkapan Tanggung Jawab Sosial melalui Laman Resmi Perusahaan terhadap Nilai Perusahaan - Santiara Dewi, Rivanti; Sudaryati, Erina (E-Jurnal Akuntansi, 2020)
The development of the internet in Indonesia in 2018 is quite rapid. The use of the company's official website can be a medium for companies to disclose and inform the company's social responsibility to stakeholders. Companies that carry out corporate social responsibility, the company's share price will increase, in this case an increase in share price is a reflection of an increase in corporate value. The purpose of this study was to determine whether disclosure of social responsibility carried out on the company website affects the value of the company, with a sample of 93 high profile industry companies listed on the Indonesia Stock Exchange in 2018, with a sampling technique using purposive sampling. The results found that the disclosure of corporate social responsibility made through the company's official website has no effect on the firm value. Keywords: CSR; Official Website; Firm Value; High Profile Industry.